Designing a research infrastructure on dietary intake and its determinants. Issue 3 (10th August 2018) - Bogaardt, M.‐J.; Geelen, A.; Zimmermann, K.; Finglas, P.; Raats, M. M.; Mikkelsen, B. E.; Poppe, K. J.; van't Veer, P.
Abstract: Research on dietary intake and its determinants is crucial for an adequate response to the current epidemic of diet‐related non‐communicable chronic diseases. In order to respond to this challenge, the RICHFIELDS project was tasked with designing a research infrastructure (RI) that connects data on dietary intake of consumers in Europe, and its determinants, collected using apps and wearable sensors, from behavioural laboratories and experimental facilities and from other RIs. The main output of the project, an RI design, describes interfaces (portals) to collect data, a meta‐database and a data‐model to enable data linkage and sharing. The RICHFIELDS project comprises three phases, each consisting of three work packages, and an overarching methodological support work package. Phase 1 focused on data generated by consumers ( e.g . collected by apps and sensors) relating to the purchase, preparation and consumption of food. Phase 2 focused on data generated by organisations such as businesses ( e.g . retail data), government ( e.g . procurement data) and experimental research facilities ( e.g . virtual supermarkets). Phases 1 and 2 provided Phase 3 with insights on data types and design requirements, including the business models, data integration and management systems and governance and ethics. The final design will be used in the coming years to build an RI for the scientific research community, policy makers and businesses in Europe. The RI will boost interdisciplinary multi‐stakeholder research through harmonisation and integration of data on food behaviour.